2021
DOI: 10.1155/2021/5609563
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mast Cells in Oral Potentially Malignant Disorders and Oral Squamous Cell Carcinoma

Abstract: Background. Oral squamous cell carcinoma (OSCC) and oral potentially malignant disorders (OPMDs) are epithelial-derived pathologies which share inflammation as a common initial pathogenic-inducing state. Mast cell is a key immune modulating cell which is primarily involved in initiation and propagation of inflammation. The role of mast cell in OPMDs and OSCC has been an established fact; however, its definitive pathogenic correlation is still under study. The objective of the study was to evaluate the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Histamine and its receptors play critical roles in several cancer-associated processes in tumor microenvironment, where mast cells (MCs) is a major source of histamine. Previous reports indicated that numbers of MCs are higher among OPMDs and OSCC compared to normal oral mucosa [ 39 ]. The MCs mainly located at the lamina propria surrounding the tumor invasive front of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine and its receptors play critical roles in several cancer-associated processes in tumor microenvironment, where mast cells (MCs) is a major source of histamine. Previous reports indicated that numbers of MCs are higher among OPMDs and OSCC compared to normal oral mucosa [ 39 ]. The MCs mainly located at the lamina propria surrounding the tumor invasive front of OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells were also increased in leukoplakia, lichen planus and actinic cheilitis [47,[53][54][55][56][57][58]. Mechanisms by which MCs might contribute to malignant progression are still not well understood [52,59]. Piecemeal degranulation is an unconventional secretory pathway char-acterized by vesicular transport of small packets of selected materials from the cytoplasmic secretory granules to the cell surface and might represent one of the main mechanisms by which MCs contribute to cancer progression.…”
Section: Mast Cellsmentioning
confidence: 99%
“…Piecemeal degranulation is an unconventional secretory pathway char-acterized by vesicular transport of small packets of selected materials from the cytoplasmic secretory granules to the cell surface and might represent one of the main mechanisms by which MCs contribute to cancer progression. These granules may be enriched of cytokines, proteases, arachidonic acid derivates and growth factors, representing a heterogeneous phenotypic expression of MCs [59][60][61][62]. A systematic review on this topic showed that the highest number of MCs was found in OPMD while their presence declined in OSCC.…”
Section: Mast Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that more blood vessels and MCs are found in the environment of OSCC compared to healthy oral mucosa, supporting the hypothesis that MCs have a tumor-promoting effect in OSCC by inducing angiogenesis [ 10 ]. In contrast, MC density has recently been shown to decrease from oral potentially malignant disorders (OPMD) to OSCC [ 11 ], and increased vascularity in OSCC appears to be inversely related to MC density [ 12 , 13 ]. These findings suggest a protective role of MCs in OSCC.…”
Section: Introductionmentioning
confidence: 99%